Comments on: Implications of structural variations in the human sacrum: why is an anatomical classification crucial? - García Coronado, Juan Mario; Espinosa Uribe, Abraham G.; Vílchez Cavazos, José Félix; Quiroga Garza, Alejandro; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (2017)
We sincerely appreciate the work done by Mahato [1] in which a qualitative classification of the sacrum is done to determine the number of segments, position of auricular surfaces, symmetry and abnormalities. This work is of the utmost importance since it is crucial for several surgical interventions and at the same time correlates certain pathologies with the morphology, mostly low back pain